2001
DOI: 10.1177/152660280100800610
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Color Duplex Examination of Aortic Endograft Patients with Suprarenal Stents

Abstract: ICDU is a simple and affordable method that seems well suited to periodic screening in patients with suprarenal stents. Longer follow-up with a larger number of patients is needed before definite conclusions can be drawn about the effect of suprarenal stenting on renal circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…22 The SMA, celiac axis, and renal arteries are physically close and normally spaced within 2 cm of each other. It has been reported that nearly 50% of patients who received a device with a suprarenal component had most of these visceral branches affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The SMA, celiac axis, and renal arteries are physically close and normally spaced within 2 cm of each other. It has been reported that nearly 50% of patients who received a device with a suprarenal component had most of these visceral branches affected.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the potential complications of suprarenal stent-grafting are the reduction in the cross-sectional area of the branch vessel ostia by a stent strut and the deposition of endothelial cells with matrix or neointimal hyperplasia around the stent. 22 The SMA, celiac axis, and renal arteries are physically close and normally spaced within 2 cm of each other. It has been reported that nearly 50% of patients who received a device with a suprarenal component had most of these visceral branches affected.…”
Section: Discussionmentioning
confidence: 99%
“…From early in our experience, the use of devices with suprarenal fixation allowed us to treat necks shorter <10 mm, with a degree of tortuosity and conicity but still stay within the manufacturers' IFU. Despite initial concerns about suprarenal stent struts impinging the renal ostium, the risk of embolization, 59 or peri-strut neointimal hyperplasia, 60 we, like previous authors, 61 successfully used suprarenal fixation without any adverse effects on renal function even after 4 years' follow-up. 17…”
Section: Discussionmentioning
confidence: 63%
“…Despite initial concerns about suprarenal stent struts impinging the renal ostium, the risk of embolization, 59 or peri-strut neointimal hyperplasia, 60 we, like previous authors, 61 successfully used suprarenal fixation without any adverse effects on renal function even after 4 years' follow-up. 17 Leurs et al 62 have analyzed the EUROSTAR registry data and reported that neck lengths ,15 mm predispose to increased risk of short-and midterm proximal endoleaks post EVAR.…”
Section: ¤ ¤mentioning
confidence: 88%
“…Stent wires cross the renal artery ostia and they might impair the blood flow or the crosssectional area [9]. However, the renal arteries remained patent permitting adequate blood supply to the kidneys [12,13]. The hereby observed cleanliness of the stent wires that cross the ostia of the renal artery support the biofonctionality, the biocompatibility and the biodurability of this transrenal concept graft.…”
Section: Discussionmentioning
confidence: 76%